A Study on the Impact of Occupational Fatigue on Human Performance among Oil and Gas Workers in Indonesia - Dahlan, Achmad; Widanarko, Baiduri (UI Scholars Hub, 2022)
Occupational fatigue is a serious problem since it may cause several issues, including deteriorating human performance. Some major accidents in the oil and gas industries were associated with the lack of human performance due to occupational fatigue. This study aimed to analyze the impact of occupational fatigue on human performance among oil and gas workers in Indonesia. This study used a cross-sectional design using a self-administered validated questionnaire to gather information on demographic (gender and age), work characteristics (work rotation, work duration, shift work model, day/night shift, job position), sleep debt, sleep quality, occupational (acute and chronic) fatigue, and at-risk behavior as the indicator of human performance. In this study, a total of 1,650 workers from different fields (production, drilling, well service, construction, and administration/office) participated. This study showed that occupational fatigue (both chronic and acute) significantly impacted human performance, and occupational fatigue conditions decreased human performance. This implied that managing occupational fatigue may prevent deteriorating human performance.